Quasi-static mechanical properties of treated and untreated sisal fibre reinforced epoxy resin composites - Webo, Wilson Wachuli (Vaal University of Technology, 2017)
Sisal is a vegetable fibre extracted from the leaves of Agave Sisalana. The fibre is long, bold and creamy white in colour besides being exceptionally strong. It can be used for making agricultural and parcelling twines of various kinds as well as ropes, sacks, carpet and upholstery. The primary purpose of this research was to study and evaluate the use of sisal as a reinforcing fibre in both treated and untreated forms with epoxy resin matrices. The casting process employed during the composite production was the the vacuum infusion. The effects of both the treated sisal fibre-epoxy resin composites and the untreated sisal fibre-epoxy resin composites on the tensile strength and stiffness, flexural strength and stiffness, impact toughness, shear strength, compression strength and hardness were evaluated. Finally, the occurrence of transverse matrix fracture and fibre pull-out were also studied. It was found that the quasi-static mechanical properties of both the treated sisal fibre-epoxy resin composites and the untreated sisal fibre-epoxy resin composites improved with increases in reinforcement weight fractions. Further, fibre surface treatment on the sisal fibres and the attendant increase in the interfacial bond also resulted into improved quasi-static mechanical properties of the treated sisal fibre-epoxy resin composites when compared to untreated sisal fibre-epoxy resin composites.
M. Eng. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Fibre; Sisal fibre; Quasi-static mechanical properties; Epoxy resin composites; Dissertations, Academic -- South Africa.; Sisal (Fiber).; Fiber plants.; Polymeric composites.; Epoxy resins.; Composite materials -- Mechanical properties.; Sisal (Plant).